2021
DOI: 10.1088/1742-6596/1811/1/012128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise and supplementation virgin coconut oil on lipid profile

Abstract: Dyslipidemia and sedentary lifestyle are risk factors for atherosclerotic heart disease. The research objective was to determine the effect of aerobic exercise and virgin coconut oil supplementation on the lipid profile of obese women. The research subjects were 20 women with obesity, divided into two groups, namely the experimental group (doing aerobic exercise and VCO supplementation) and the control group (only doing aerobic exercise) with the 43.55±2.21 age, 154.75±0.05 height, 75.75±1.44 weight and 31.69±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…People with high levels of bad cholesterol and low physical activity are more likely to develop heart disease. Aerobics formation transformation route simulation taking virgin coconut oil supplementation can improve the lipid profile of obese women, according to this review [14]. Virtual reality in aerobics formation route simulation exercises in AI has no substantial physiologic or motivational advantages over traditional aerobic exercise [15].…”
Section: Summary Of Aerobics Formation With Artificial Intelligence A...mentioning
confidence: 96%
“…People with high levels of bad cholesterol and low physical activity are more likely to develop heart disease. Aerobics formation transformation route simulation taking virgin coconut oil supplementation can improve the lipid profile of obese women, according to this review [14]. Virtual reality in aerobics formation route simulation exercises in AI has no substantial physiologic or motivational advantages over traditional aerobic exercise [15].…”
Section: Summary Of Aerobics Formation With Artificial Intelligence A...mentioning
confidence: 96%
“…In a higher-level study, the intake of 30 mL of VCO daily increased HDL levels in healthy people [ 11 ]. Another clinical study showed that VCO taken daily for 8 weeks reduced TC and TG levels in women with obesity [ 12 ]. The biological efficacy of VCO is due to its high polyphenol content such as ferulic acid, vanillic acid, p- coumaric acid, syringic acid, and caffeic acid.…”
Section: Introductionmentioning
confidence: 99%